THE ROLE OF FAMILY GUESTHOUSES IN THE DEVELOPMENT OF THE TOURISM INDUSTRY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article examines the role of family guesthouses in the development of the tourism industry. The study analyzes the economic, social, and cultural significance of family guesthouses, their contribution to tourism infrastructure, and their importance in promoting sustainable tourism development. The research also evaluates the impact of family guesthouses on rural tourism, eco-tourism, employment generation, and regional economic growth. Furthermore, the study identifies major challenges related to service quality, management practices, digital technologies, and marketing activities. Based on the research findings, practical recommendations for improving the effectiveness and competitiveness of family guesthouses in the tourism industry are proposed.